Analisis Komparatif atas Kitab Asbab Al-wurud Al-Hadis: Studi terhadap Al-Luma’ Karya Al-Suyuti dan Al-Bayan Karya Al-Husaini - Dhiwa Adlani Nahar (ISME : Journal of Islamic Studies and Multidisciplinary Research, 2025)
This study comparatively discusses two classic works that focus on the study of Asbab Al-Wurud Al-Hadis, namely Al-Luma fi Asbab Al-Hadis by Jalaluddin Al-Suyuti and Al-Bayan wa Al-Ta'rif Fii Asbab Al-Wurud Al-Hadis Al-Syarif by Al-Husaini. Using a qualitative research method based on a literature study, this article explores the differences and similarities in the writing structure, compilation method, as well as the scope of hadith content in the two books. The results of the study show that Al-Luma' is more systematic in its arrangement by fiqh chapter and focuses on the micro Asbāb Al-Wurūd, while Al-Bayān has a much broader scope of traditions with more than 1800 traditions and explains both micro and macro Asbāb al-Wurūd. Based on the analysis, Al-Bayān is considered superior in its comprehensiveness and coverage of the historical causes of the traditions. This study emphasises the importance of the study of asbāb al-wurūd in understanding the context, purpose and applicability of traditions more comprehensively.